Dependence of Ge/Si avalanche photodiode performance on the thickness and doping concentration of the multiplication and absorption layers - Deeb, Hazem; Khomyakova, Kristina I.; Kokhanenko, Andrey P.; Douhan, Rahaf M. H.; Lozovoy, Kirill A. (Inorganics)
In this article, the performance and design considerations of the planar structure of germanium on silicon avalanche photodiodes are presented. The dependences of the breakdown voltage, gain, andwidth, responsivity, and quantum efficiency on the reverse bias voltage for different doping concentrations and thicknesses of the absorption and multiplication layers of germanium on the silicon avalanche photodiode were simulated and analyzed. The study revealed that the gain of the avalanche photodiode is directly proportional to the thickness of the multiplication layer. However, a thicker multiplication layer was also associated with a higher breakdown voltage. The bandwidth of the device, on the other hand, was inversely proportional to the product of the absorption layer thickness and the carrier transit time. A thinner absorption layer offers a higher bandwidth, but it may compromise responsivity and quantum efficiency. In this study, the dependence of the photodetectors' operating characteristics on the doping concentration used for the multiplication and absorption layers is revealed for the first time.